LANGUAGE FUNCTION IN HILLARY CLINTON’S SPEECHES ON YOUTUBE - Uli, Bunga Darma; Syaputri, Komala Dwi (Direktorat Riset dan Pengabdian kepada Masyarakat, Universitas Bina Darma, 2018)
This study discussed the language function in Hillary Clinton?s speeches on YouTube. The objectives of this study were to identify and describe the types of the language function found in her speeches as well as to describe the meaning of every language function she used in her speeches. There were four of her speeches were analyzed in the study. Moreover, the descriptive qualitative approach was used in analyzing the speeches. The data were classified into six types of language function according to Jacobson?s theory: referential function, emotive function, conative function, phatic function, metalingual function, and phoetic function. There were 8 types of language function and meaning expressions found in the analyzed speeches. Each type of it was not equally found. The highest was 3 (40%) referential function, 2 (20%), phoetic function, 1 (10%) emotive function, 1 (10%) phatic function, and 1 (10%) metalingual function. The result of the study showed that all the analyzed speeches contained language function. Therefore, it was clear that Hillary instilled the language function in order to make her speeches understandable and meaningful to the audience.